Religion-Based Gender Mainstreaming and Cultural-Political Transformation: A Study of Nyai Aqidah Usymuni's Leadership in Sumenep - Ahmadi; Ali, Fida Ruhiyah (Jurnal Studi Gender dan Anak, 2025)
Gender mainstreaming in Indonesia, especially in rural areas, still faces serious challenges due to the dominance of patriarchal norms that limit women's access to education, health, and economic opportunities. This condition reinforces gender inequality and hinders women's welfare. This study aims to analyze the role of Nyai Aqidah Usymuni in gender mainstreaming in Sumenep, East Java, highlighting the significance of female actors in Islamic boarding schools in promoting religious-based social transformation. The study uses a qualitative approach with a case study design. Data were collected through interviews, non-participatory observation, and document analysis. Findings show that Nyai Aqidah implements religion-based gender mainstreaming that operates in the cultural and political spheres, supported by an intersectional and institutional approach. Through Pesantren education, reinterpretation of gender-equitable Islamic teachings, and advocacy for women's protection, she is able to challenge patriarchal structures in a contextual manner. However, this study is limited to a single case study and has not measured the long-term impact on public policy changes and gender equality indicators quantitatively. [Pengarusutamaan gender di Indonesia, khususnya di wilayah pedesaan, masih menghadapi tantangan serius akibat dominasi norma patriarkis yang membatasi akses perempuan terhadap pendidikan, kesehatan, dan kesempatan ekonomi. Kondisi ini memperkuat ketimpangan gender dan menghambat kesejahteraan perempuan. Penelitian ini bertujuan menganalisis peran Nyai Aqidah Usymuni dalam pengarusutamaan gender di Sumenep, Jawa Timur, dengan menyoroti signifikansi aktor perempuan pesantren dalam mendorong transformasi sosial berbasis keagamaan. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara, observasi nonpartisipatif, serta analisis dokumen. Temuan menunjukkan bahwa Nyai Aqidah menerapkan pengarusutamaan gender berbasis keagamaan yang beroperasi dalam ranah kultural dan politik, didukung oleh pendekatan interseksional dan kelembagaan. Melalui pendidikan pesantren, reinterpretasi ajaran Islam yang adil gender, serta advokasi perlindungan perempuan, ia mampu menantang struktur patriarki secara kontekstual. Namun, penelitian ini terbatas pada satu studi kasus dan belum mengukur dampak jangka panjang terhadap perubahan kebijakan publik dan indikator kesetaraan gender secara kuantitatif].